Pengaruh Academic Self-Efficacy, Peer Support dan Fasilitas Belajar terhadap Hasil Belajar Akuntansi Keuangan Kelas XI Akuntansi SMKN 1 Jombang - Kharisma Febrianti; Luqman Hakim (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This research is motivated by data on financial accounting learning outcomes that show that approximately 50% of students still obtain scores below the standard with the Learning Objective Achievement Criteria (KKTP) of 75. Financial accounting learning outcomes are thought to be influenced by several factors, both internal factors such as academic self-efficacy, and external factors such as peer support and learning facilities. This study aims to analyze the influence of academic self-efficacy, peer support and learning facilities on financial accounting learning outcomes of class XI Accounting students of SMK Negeri 1 Jombang. This study uses a quantitative approach with an ex post facto research type. The research sample amounted to 142 students selected using total sampling technique with data collection techniques using questionnaires. Data analyze was carried out using descriptive statistical tests, classical assumption tests, and hypothesis tests with the help of IBM SPSS Statistics 25. The results of the study indicate that academic self-efficacy has a significant positive effect on learning outcomes, while peer support and learning facilities do not have a significant positive effect on learning outcomes, and academic self-efficacy, peer support and learning facilities simultaneously have a significant effect on learning outcomes. It's concluded that a high level of academic self-efficacy will significantly improve students financial accounting learning outcomes.